2008
DOI: 10.1128/aem.00961-08
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Electrode as a Sole Electron Donor for Reductive Dechlorination of Tetrachlorethene by Geobacter lovleyi

Abstract: The possibility that graphite electrodes can serve as the direct electron donor for microbially catalyzed reductive dechlorination was investigated with Geobacter lovleyi. In an initial evaluation of whether G. lovleyi could interact electronically with graphite electrodes, cells were provided with acetate as the electron donor and an electrode as the sole electron acceptor. Current was produced at levels that were ca. 10-fold lower than those previously reported for Geobacter sulfurreducens under similar cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(162 citation statements)
references
References 31 publications
10
150
1
1
Order By: Relevance
“…G. lovleyi and Anaeromyxobacter dehalogenans have been shown to reduce chlorinated compounds with as electrode as the sole source of electrons [142,143]. Field trials have also shown that electrons provide by an electrode can improve uranium removal in contaminated sites [127].…”
Section: Cathode Interactionsmentioning
confidence: 99%
“…G. lovleyi and Anaeromyxobacter dehalogenans have been shown to reduce chlorinated compounds with as electrode as the sole source of electrons [142,143]. Field trials have also shown that electrons provide by an electrode can improve uranium removal in contaminated sites [127].…”
Section: Cathode Interactionsmentioning
confidence: 99%
“…Consequently, it is likely that bacteria reducing nitrate at cathodes powered by anodic reactions access electrons from the cathode and not through hydrogen. Our current knowledge of bacterial denitrification reactions relevant to BES cathodes is based on pure-culture studies of chemolithotrophic denitrification coupled to inorganic electron donors (Fernández et al, 2008;Weber et al, 2006) and cathodes as electron donors for anaerobic respiration (Gregory et al, 2004;Thrash et al, 2007;Strycharz et al, 2008;Thrash and Coates, 2008;He et al, 2009). Presently, only two studies examined microbial biofilm communities in denitrifying BESs (Gregory et al, 2004;Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria achieve extracellular electron transfer through a variety of different mechanisms and can be utilized to produce power in microbial fuel cells [17][18][19], produce chemicals in microbial electrolysis cells [20][21][22], and remediate organic contaminants in the subsurface [23][24][25][26]. While humans have successfully exploited the ability of microbes to perform extracellular electron transfer in bioengineered systems, the role that extracellular electron transfer plays in natural environments, such as soils, is less clear [27].…”
Section: Introductionmentioning
confidence: 99%